2007
DOI: 10.1001/archpsyc.64.4.419
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Treatments for Bipolar Depression

Abstract: Context: Psychosocial interventions have been shown to enhance pharmacotherapy outcomes in bipolar disorder.Objective: To examine the benefits of 4 disorderspecific psychotherapies in conjunction with pharmacotherapy on time to recovery and the likelihood of remaining well after an episode of bipolar depression.Design: Randomized controlled trial.Setting: Fifteen clinics affiliated with the Systematic Treatment Enhancement Program for Bipolar Disorder.Patients: A total of 293 referred outpatients with bipolar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
161
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 460 publications
(171 citation statements)
references
References 46 publications
5
161
0
2
Order By: Relevance
“…For acute bipolar depression in adults, an intensive FFT (up to 30 sessions; mean 14) out‐performed a three‐session control condition,94 although this study was limited by the caveats identified for CBT and IPSRT. Given that the original creation of FFT targeted factors related to depression, it may have specific antidepressant activity, which is also suggested by reduced depression relapse in maintenance studies.…”
Section: Foundations Of Managementmentioning
confidence: 99%
“…For acute bipolar depression in adults, an intensive FFT (up to 30 sessions; mean 14) out‐performed a three‐session control condition,94 although this study was limited by the caveats identified for CBT and IPSRT. Given that the original creation of FFT targeted factors related to depression, it may have specific antidepressant activity, which is also suggested by reduced depression relapse in maintenance studies.…”
Section: Foundations Of Managementmentioning
confidence: 99%
“…Family-focused therapy, interpersonal and social rhythm therapy and life goals program appear to be more effective when patients are acutely ill, whereas CBT and group psychoeducation showed better results when started during a period of remission [17]. CBT has been applied in many controlled studies of patients with BD [15,18,19,20,21,22,23,24]. When used in individuals as opposed to groups, CBT showed efficacy in the management of depressive episodes, reducing the time during which the patient was ill and the number of BD episodes, although all controlled trials have used different CBT models and criteria to select patients [25].…”
Section: Introductionmentioning
confidence: 99%
“…If so, measurement of EE has the potential to be more than an indirect assessment of degree of family burden. Rather, it can help identify a constellation of attitudes and behaviors that can be addressed therapeutically with positive effects on patient adjustment (Miklowitz, et al, 2007).…”
Section: Central Relational Processesmentioning
confidence: 99%
“…However, there is growing evidence of the effectiveness of several specific approaches to family intervention. For example, the combination of family-focused therapy (FFT) and pharmacotherapy delays relapses and reduces symptom severity among patients followed over the course of 1 to 2 years (see Miklowitz, 2007, for a review). Likewise, there is initial evidence that family-based interventions provided in the prodrome of a disorder may help alleviate its severity.…”
Section: Central Relational Processesmentioning
confidence: 99%